A Renewable Relationship between Epilepsy and Quinazolinones - H. S. Al-Salem; T. O. Mirgany (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
Epilepsy is a global public health issue requiring a global response. Epilepsy is present everywhere and affects people of various ages, genders, ethnicities, and social backgrounds, regardless of geographical locations. The epileptic state is typically caused by excessive cortical neuron discharge in the cortical region of the brain. The first step toward a proper epilepsy diagnosis, course of treatment, and prognosis is understanding the classification of epileptic episodes. Specific drugs or surgical techniques frequently work better on particular seizure types or disorders. Multidrug resistant syndrome and refractory epilepsy are the biggest challenge in treatment of epilepsy, they lead to defect access of Anti-Epileptic Drugs AEDs to their target in CNS. Moreover, the marketed drugs carry severe side effects such as drowsiness, hepatotoxicity, anemia, and teratogenicity. There is a pivotal need to discover more safe and effective drugs. Quinazolinones analogues represent molecules which are capable of binding at multiple sites with high affinity and facilitate more rapid discovery of useful medicinally active compounds. Numerous scientists from all around the world have created a number of novel quinazolinone derivatives that have been virtually screened and tested for their ability to treat various forms of seizures. They will play a crucial role in the future treatment of epilepsy.